Validity and reliability of an adapted questionnaire measuring acceptance of traditional Chinese medicine among cancer patients - Sue, PH; NG, FL; Foo, CN; Tham, JS; Zhu, X; Lim, YM (Penerbit Universiti Kebangsaan Malaysia (UKM Press), 2023)
Acceptance of traditional chinese medicine (TCM) treatment is important in cancer patients to improve treatment efficacy, reduce side effects and prolong prognosis and survival rate. However, such studies and validated instruments that assess the acceptance of TCM treatment in Malaysia are limited. This study aimed to evaluate the validity and reliability of the acceptance of the TCM treatment questionnaire based on applying the Theory of Planned Behaviour. The validation study was conducted in two phases. The first phase included content validation, adaptation and face validity using the Survey Validation Rubric for Expert Panel (VREP). The second phase included construct reliability by using Cronbach alpha. The first phase validation of the questionnaire met expectations from the experts’ panel with a score of 3.33. In phase two, 78 patients were included in the analysis. All constructs achieved a Cronbach Alpha >0.8, showing good reliability of the questionnaire. This study demonstrated good validity and reliability of the major constructs in the acceptance of the TCM questionnaire. Our results showed that the acceptance of the TCM questionnaire was a reliable instrument that could be applied to evaluate the acceptance of TCM treatment among cancer patients.